Analysis of Cesarean Section Clinical Pathway Compliance at a Private Hospital in Yogyakarta - Beta Haninditya; Tri Murti Andayani; Nanang Munif Yasin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
This study aims to analyze the relationship between the compliance with the implementation of clinical pathways to therapeutic outcomes (ILO events, length of stay, pain intensity) and the total real cost of cesarean section patients. The study was conducted at a type C private hospital in Yogyakarta. This study is a non-experimental analytical study (observational analytic) with a cross sectional design using a retrospective data collection method and analyzed using Chi square test and non parametric regression test. Descriptive analysis for compliance with the implementation of clinical pathways was carried out by assessing the compliance of each care point contained in the clinical pathway section of the cesarean consisting of 12 points of care and will be grouped into two categories namely low compliance category with the average compliance value for clinical pathway <85% and good compliance with the average compliance value for clinical pathway ≥85%. Descriptions of adherence to the implementation of clinical pathway cesarean section each patient showed that as many as 686 patients (98%) had a good average compliance score and 14 patients (2%) had a low average compliance score. Outcome description 700 patients with cesarean section were found 1 patient experienced ILO, LOS according to clinical pathway (≤3 days) as many as 620 patients and 700 patients with pain scale ≤3. The results of the analysis of the relationship between the compliance and the implementation of the clinical pathway to the outcome of therapy (ILO events, length of stay, and pain intensity) showed the existence of a compliance relationship to the implementation of the clinical pathway with a value of p<0.05. The analysis of the relationship between the compliance to the implementation of the clinical pathway and the total real costs shows the relationship between the compliance   with   the   implementation   of  the  caesarean  section  clinical  pathway  at  a  type  C  private hospitals in Yogyakarta with the total real costs with p value of 0,000 and r value of 0.014.